Alopecia areata treated with topical and systemic brevilin A: A case series. Issue 2 (10th February 2021) - Muscianese, Marta; Magri, Francesca; Leoncini, Pierpaolo; Fortuna, Maria Caterina; Caro, Gemma; Rossi, Alfredo
Abstract: Alopecia areata (AA) is an autoimmune T CD8 cell mediated condition clinically characterized by hair loss from single or few small patches to complete hair loss. The management of AA is challenging and all available therapies does not ensure a long‐term remission. To assess the safety and efficacy of both systemic and topical brevilin A, a natural compound, in AA patients not responding to other treatments. After obtaining informed consent, we administered off‐label brevilin A to 13 adult patients affected by AA, for a period ranging from 6 to 18 months. Medical records for each patient and the severity of alopecia tool (SALT) score before and after brevilin A administration were recorded. The mean SALT score of our patients was 81.03 (SD 34.9) at baseline and 75.8 (SD 37.4) after brevilin A therapy, meaning no statistically significant improvement was observed ( P = .2385 Paired t test). However, three multifocal AA (MAA) patients out of four attained an improvement (75%) suggesting that brevilin A may be represent an alternative therapy in this form of AA. Authors conclude that brevilin A could represent in the future a possible effective treatment in MAA forms but further studies are required.